Complications and clinical factors associated with pediatric percutaneous endoscopic gastrostomy in a Colombian cohort - Cuadros Mendoza, Carlos Augusto; Rosero Portilla, Mario Javier; Pico Quintero, Verónica; Manrique-Hernández, Edgar Fabián; Hurtado-Ortiz, Alexandra; Licht-Ardila, Maricel; Mendoza-Monsalve, Alejandra (Frontiers in Pediatrics, 2025)
IntroductionMalnutrition significantly impairs both physical and cognitive function, increasing the risk of morbidity and mortality, especially in patients lacking a safe and effective route for enteral nutrition. Percutaneous endoscopic gastrostomy offers a minimally invasive solution for long-term enteral nutrition in pediatric patients, with a lower risk of perioperative complications compared to surgical alternatives.ObjectiveTo evaluate the frequency, timing, and clinical factors associated with postoperative complications following pediatric percutaneous endoscopic gastrostomy.MethodsA retrospective analytical cohort study was conducted, including pediatric patients (≤18 years) who underwent Percutaneous endoscopic gastrostomy placement between January 2018 and December 2024. Bivariate analyses and Kaplan–Meier survival curves were used to assess the frequency of complications and complication-free survival time.ResultsA total of 86 pediatric patients underwent Percutaneous endoscopic gastrostomy during the study period, of whom 12 (14%) experienced major postoperative complications. The median age was 4.53 years (interquartile range: 1.56–9.46 years). The most frequent major complication was Buried Bumper Syndrome, observed in 9 patients (10.47%). Minor complications included mild peristomal infection (8.14%) and feeding intolerance (5.81%). A complication-free survival of 96.73% (95% CI: 87.26–99.19) by day 12 and 69.35% (95% CI: 45.33–84.43) by day 40 was determined.DiscussionThis study underscores the importance of systematic nutritional assessment and optimized post-operative care to reduce complications following PEG in pediatric patients. The high incidence of Buried Bumper Syndrome calls for more stringent follow-up protocols, especially in resource-limited settings. Close monitoring during the early post-operative period can prevent complications.